1994
DOI: 10.1046/j.1537-2995.1994.34994378275.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of intravenous immunoglobulin in the treatment of human immunodeficiency virus‐associated thrombocytopenia

Abstract: IVIG consistently raises platelet counts in patients with HIV-associated thrombocytopenia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…43,44 Analysis of platelet counts in anti-TER-119 antibody-treated thrombocytopenic mice indicated that the monoclonal antibody protected against thrombocytopenia for at least 4 days after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…43,44 Analysis of platelet counts in anti-TER-119 antibody-treated thrombocytopenic mice indicated that the monoclonal antibody protected against thrombocytopenia for at least 4 days after treatment.…”
Section: Discussionmentioning
confidence: 99%
“…To evaluate our results we chose the criteria proposing PR not only as an increase > 50 × 10 9 /l in the PC but also raising the initial PC at least twice (raising the PC > 50 × 10 9 /l may be properly called PR for an initial PC < 20 × 10 9 /l but this is not true if the initial PC is 48 × 10 9 /l) [12]. In AIDS-free HIV+ cases, IR to IVIg is fast [33], ranging from 71% to 100% with a failure rate of 29% [13,21,34]. Previous reports described a few AIDS patients [21,23,26,27,35], and based on one patient it was suggested that lower response rates of HIV-Thr to IVIg would more likely be seen in AIDS compared to AIDSfree HIV+ individuals [26].…”
Section: Discussionmentioning
confidence: 99%
“…Initially, high doses of IVIg for HIV-Thr were successfully used in five-or two-day courses [24,29,34]. Because the half life of IVIg preparations range from 15 to 58 days [49,50], we thought that weekly infusions might maintain adequate plasma levels of Ig.…”
Section: Discussionmentioning
confidence: 99%
“…IV Ig is indicated in patients with thrombocytopenia secondary to HIV infection unresponsive to antiretroviral therapy, and the management should not differ from that for the idiopathic form. [21,22] Immune red cell destruction has also been a focus of interest for immunoglobulin therapy. Controlled studies have Key steps in modern manufacturing focus on: (i) the removal of substances associated with side-effects, e.g.…”
Section: Haematologymentioning
confidence: 99%